Translation Teaching, For Research to the Classroom : A Handbook For Teachers - Sonia Colina (McGraw-Hill Higher Education, 2003)
This book is about the teaching of translation. Here we are concered with translation as a commnicative activity, mostly practice by professional translator and motivated by the need of source audience to communicate with audience that speaks a different lanuage.